The embodiment of the World War I events in Belarusian poetry of the 1920–30s - Tratsiak, Zoya I. (Journal of the Belarusian State University. Philology, 2023)
The article oﬀers a new approach to the understanding of Belarusian poetry of the 1920–30s, dedicated to the World War I. The stereotype about the minimal presence of the World War I theme in Belarusian literature is refuted. A modern reading of the corpus of poems by native authors (Zmitrok Byadulya, Ales’ Garun, Yakub Kolas, Yanka Kupala, Yanka Maslennik, Yazep Pushcha, Yazep Shpet, etc.) was carried out. Based on rich factual material, three perspectives in the embodiment of the mentioned above topic are distinguished (artistic image of the front, artistic image of the refugees, artistic image of the rear). The idea of complementarity of diﬀerent genres of Belarusian literature, which embodied the events of 1914–1918, is proven. The antiwar pathos of Belarusian poetry about the World War I is confrmed. The main approaches  to the interpretation of Belarusian poetry about the World War I in native literary studies of the 1920–30s and at the border of the 20th and 21st centuries are considered.
Keywords: Belarusian literature; the World War I; complementarity; antiwar poetry; thematic diversity; frontline; rear; refugees